Používání soli s jódem při výrobě výrobků živočišného původu v ČR - Pechan, Lydie; Malena, Milan; Trlíková, Andrea (Optimální působení tělesné zátěže a výživy, 2002)
The importance of use of iodised salt in the manufacture of foodstuffs for prevention of iodine deficit and for satisfactory supply of iodine to population is obvious, and increases proportionately to the increase in cosumption of manufactured foodstuffs. It is also a very effective and ready method of effectively influencing the actual saturation of population, which was proved e.g. by the current results of satisfactory to optimal saturation (above 100ug iodine/l of urine) in 96% of a group of 578 children aged 10-12 from 11 districts in the Czech Republic in 2001. Epidemiological studies showed a significant improvement in iodine saturation of our citizens, which correlates with increased percentage of manufacturers of foodstuffs of animal origin who use salt or nitrous mixture with iodine, from 56% before intervention in mid-1999 up to 85% in 2002. The effort of all participants - manufacturers as well as experts can thus significantly improve the physical and intellectual quality of our population.
Keywords: kuchyňská sůl; masný průmysl; Meat-Packing Industry; Primary Prevention; potravinářský průmysl; masné výrobky; potravinářská technologie; jod; Nitrites; primární prevence; Iodine; Food Technology; dusitany; označování potravin; Data Interpretation, Statistical; Sodium Chloride, Dietary; Food, Fortified; fortifikované potraviny; Czech Republic; Meat Products; Food Industry; Česká republika; Food Labeling; interpretace statistických dat